2009
DOI: 10.1104/pp.108.130369
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma virens, a Plant Beneficial Fungus, Enhances Biomass Production and Promotes Lateral Root Growth through an Auxin-Dependent Mechanism in Arabidopsis      

Abstract: Trichoderma species belong to a class of free-living fungi beneficial to plants that are common in the rhizosphere. We investigated the role of auxin in regulating the growth and development of Arabidopsis (Arabidopsis thaliana) seedlings in response to inoculation with Trichoderma virens and Trichoderma atroviride by developing a plant-fungus interaction system. Wild-type Arabidopsis seedlings inoculated with either T. virens or T. atroviride showed characteristic auxin-related phenotypes, including increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
498
0
25

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 848 publications
(544 citation statements)
references
References 44 publications
21
498
0
25
Order By: Relevance
“…have beneficial effects on plants. For instance, there are commercial agricultural products containing T. atroviride, T. harzianum and T. hamatum (Ha, 2010) that promote plant growth (Chang et al ., 1986; Gravel et al ., 2007; Contreras‐Cornejo et al ., 2009), reduce the severity of plant diseases (Naseby et al ., 2000; Nawrocka and Malolepsza, 2013) and enhance tolerance to abiotic stresses (Bae et al ., 2009; Montero‐Barrientos et al ., 2010; Dixit et al ., 2011; Contreras‐Cornejo et al ., 2014). In addition, Trichoderma sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…have beneficial effects on plants. For instance, there are commercial agricultural products containing T. atroviride, T. harzianum and T. hamatum (Ha, 2010) that promote plant growth (Chang et al ., 1986; Gravel et al ., 2007; Contreras‐Cornejo et al ., 2009), reduce the severity of plant diseases (Naseby et al ., 2000; Nawrocka and Malolepsza, 2013) and enhance tolerance to abiotic stresses (Bae et al ., 2009; Montero‐Barrientos et al ., 2010; Dixit et al ., 2011; Contreras‐Cornejo et al ., 2014). In addition, Trichoderma sp.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike other reported Trichoderma strains that induced IAA levels in Arabidopsis and had growth promotion capacity (Contreras‐Cornejo et al ., 2009; Martinez‐Medina et al ., 2011), T. gamsii F18 did not increase the IAA content in our studies. This result might explain the fact that no plant growth promotion effect was observed with the inoculation of this strain (data not shown) indicating a different mode of action.…”
Section: Discussionmentioning
confidence: 99%
“…The results correlate with the findings of Mendes et al [18], where isolates of Aspergillus niger FS1, Penicillium canescens FS23 and Eupenicillium ludwigii were able to solubilize all forms of P. The phosphate-solubilizing microbes showing greater solubilization (both qualitatively and quantitatively) of insoluble P under in vitro conditions were selected for field trials prior to production in bulk for ultimate transmission as a biofertilizer [16]. It is also suggested that phosphate solubilization, production of IAA, and other related compounds by the fungus will interact with plants as part of its colonization, leading to growth promotion, induced resistance, and modification of basal plant defense mechanisms [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Consecutively, the shoot and/or fruit biomass production increases. 52 For example, the yeast isolate C. tropicalis SSm-39 was able to produce IAA. 53 The inoculation of maize plants (Zea mays) with SSm-39 reduced the dose of chemical fertilizer application as well as increased the growth and yield performance of maize.…”
Section: Iaa In Fungal -Plant Interactionsmentioning
confidence: 99%
“…55 The introduction of W. saturnus to maize seedlings enhanced the growth of maize plants as indicated by increases in the dry weights and lengths of roots and shoots. 52 We previously showed that U. esculenta (strain JYC070) exhibited high IAA production, whereas Hannaella coprosmaensis (strain YL-10) produced relatively low IAA in all conditions. 26 Arabidopsis seedlings cocultivated with U. esculenta caused significant 10-fold increase in the lateral root number compared with those cocultivated with H. coprosmaensis.…”
Section: Iaa In Fungal -Plant Interactionsmentioning
confidence: 99%